Nickel-free stainless steel avoids neointima formation following coronary stent implantation - Fujiu, Katsuhito (Sci Technol Adv Mater, 2012)
SUS316L stainless steel and cobalt–chromium and platinum–chromium alloys are widely used platforms for coronary stents. These alloys also contain nickel (Ni), which reportedly induces allergic reactions in some subjects and is known to have various cellular effects. The effects of Ni on neointima formation after stent implantation remain unknown, however. We developed coronary stents made of Ni-free high-nitrogen austenitic stainless steel prepared using a N(2)-gas pressurized electroslag remelting (P-ESR) process. Neointima formation and inflammatory responses following stent implantation in porcine coronary arteries were then compared between the Ni-free and SUS316L stainless steel stents. We found significantly less neointima formation and inflammation in arteries implanted with Ni-free stents, as compared to SUS316L stents. Notably, Ni(2+) was eluted into the medium from SUS316L but not from Ni-free stainless steel. Mechanistically, Ni(2+) increased levels of hypoxia inducible factor protein-1α (HIF-1α) and its target genes in cultured smooth muscle cells. HIF-1α and their target gene levels were also increased in the vascular wall at SUS316L stent sites but not at Ni-free stent sites. The Ni-free stainless steel coronary stent reduces neointima formation, in part by avoiding activation of inflammatory processes via the Ni-HIF pathway. The Ni-free-stainless steel stent is a promising new coronary stent platform.